Clinical nursing effect of comprehensive nursing in department of respiratory medicine - Caihong Shen; Caihong Shen; Min Zhang; Min Zhang; Ting Yao; Ting Yao; Hui Sun; Hui Sun; Yantian Nie; Yantian Nie; Pengfei Song; Pengfei Song; et al. (Frontiers in Medicine)
ObjectiveTo probe the clinical effect of comprehensive nursing in department of respiratory medicine.MethodsA total of 176 patients who were diagnosed and treated in the department of respiratory medicine from January 2020 to June 2022 were chosen. Based on the random lottery method, there were 90 cases in the observation group (OG) and 86 cases in the control group (CG). Patients in the CG adopted routine nursing services, while patients in the OG adopted comprehensive nursing program. The blood gas related index levels, nursing satisfaction, quality of life scores, nursing quality, patients’ anxiety, depression and adverse events were compared between the two groups after nursing intervention.ResultsThe nursing efficiency of the OG was increased compared to the CG. The levels of PaO2 and PaCO2 in the OG were elevated relative to the CG (p < 0.05). The satisfaction of patients in the OG was enhanced in contrast to the CG (p < 0.05). The incidence rate was 2.22% in the OG and 8.48% in the CG. The nursing quality score of the OG was elevated in comparison with the CG (p < 0.05). The scores of anxiety and depression in the OG were increased compared to the CG (p < 0.05).ConclusionThe application of comprehensive nursing in the clinical nursing process of respiratory medicine department can effectively improve the patient’s nursing satisfaction, reduce the incidence of adverse events, improve the quality of nursing, and control the patient’s negative emotions, so that the effect of patients in clinical treatment can be improved and can be vigorously promoted.